Endoscopic Nipple- or Skin-Sparing Mastectomy and Immediate Breast Reconstruction with Endoscopic Harvesting of the Latissimus Dorsi Flap: A Preliminary Experience of an Innovative Technique - Yu Feng; Nan Wen; Faqing Liang; Jiao Zhou; Xiangquan Qin; Xinran Liu; Juan Li; Mengxue Qiu; Huanzuo Yang; Zhenggui Du (Hindawi-Wiley, 2022)
Background. Endoscopic nipple- or skin-sparing mastectomy (E-N/SSM) and endoscopic latissimus dorsi muscle flap (E-LDMF) harvest have been operational difficulties over decades. The aim of this study was to describe the preliminary outcomes of our novel surgical technique, which allows the performance of E-N/SSM and E-LDMF harvest for immediate breast reconstruction (IBR) through a single cosmetic axillary incision for breast cancer patients. Methods. This prospective study included 20 breast cancer patients who underwent E-N/SSM and E-LDMF harvesting through a single axillary incision in our hospital from September 2020 to June 2022. The outcomes were statistically calculated, including patient characteristics, operative data, complication rate, hospital length of stay and costs, and patient-reported outcomes. Results. A total of 20 breast cancer patients underwent our sufficiently mature novel endoscopy technique. The mean LD flap harvest time was 96.5 ± 25.3 min, the mean operation time was 262.6 ± 54.4 min, and the average length of LDMF was 26.9 ± 3.1. During the median follow-up time of 7.5 months, 4 patients developed donor-site seroma. One of them was also complicated by hypopigmentation of the nipple areola, and one of them suffered from breast cellulitis. No bleeding or flap necrosis happened. No tumor recurrence or metastasis was found until the last follow-up. In the BREAST-Q evaluation, although they gave a lower score beginning at 1-month post-operation than preoperatively (P>0.05, except for physical well-being: chest and physical well-being: back and shoulder, P<0.01), there was an uptrend at 3 months postoperatively. Because of the hidden and short incision, the mean score of the appearance scale of the SCAR-Q at 3 months post-operation was 74.2 ± 8.8. Conclusions. The novel endoscopy technique, which was first reported to perform lymph node surgery, N/SSM, and LDMF harvesting in an operation for breast cancer patients through a single axillary incision, is associated with a shorter surgery time, lower complication rates, and better patient-reported outcomes.